Incorporating neglected non-communicable diseases into the national health program—A review - Bhattacharya, Sudip; Heidler, Petra; Varshney, Saurabh (Frontiers in Public Health, 2023)
Poor nations are already facing the heat of double burden of communicable and non-communicable illnesses (NCDs), often known as chronic illnesses, which are characterized by a protracted course and are multifactorial in causation. Neglected Non-Communicable Diseases (NNCD) is likely to be one of the biggest public health challenges soon. Nearly three-quarters (31.4 million) of all NCD-related fatalities occur in developing nations, which are disproportionately affected by NCDs. In terms of morbidity and death, the "BIG FOUR" NCDs—diabetes, cancer, chronic respiratory diseases, and cardiovascular diseases—are widely acknowledged as the main contributors to global health loss. However, other NCDs account for 55% of the global burden of NCDs and are frequently disregarded in terms of premature death, increased Disability Adjusted Life Years (DALY), and decreased Quality-Adjusted Life Year (QALY). We have briefly discussed the illness burden of a few significant but the neglected NCDs in this paper.